A novel experience-based internet intervention for smoking cessation: feasibility randomised controlled trial. (December 2016) - Powell, John; Newhouse, Nikki; Martin, Angela; Jawad, Sena; Yu, Ly-Mee; Davoudianfar, Mina; Locock, Louise; Ziebland, Sue
Abstract Background The internet is frequently used to share experiences of health and illness, but this phenomenon has not been harnessed as an intervention to achieve health behaviour change. The aim of this study was to determine the feasibility of a randomised trial assessing the effects of a novel, experience-based website as a smoking cessation intervention. The secondary aim was to measure the potential impact on smoking behaviour of both the intervention and a comparator website. Methods A feasibility randomised controlled single-blind trial assessed a novel, experience-based website containing personal accounts of quitting smoking as a cessation intervention, and a comparator website providing factual information. Feasibility measures including recruitment, and usage of the interventions were recorded, and the following participant-reported outcomes were also measured: Smoking Abstinence Self-Efficacy Questionnaire, the single-item Motivation to Stop Scale, self-reported abstinence, quit attempts and health status outcomes. Eligible smokers from two English regions were entered into the trial and given access to their allocated website for two weeks. Results Eighty-seven smokers were randomised, 65 completed follow-up (75 %). Median usage was 15 min for the intervention, and 5 min for the comparator (range 0.5–213 min). Median logins for both sites was 2 (range 1–20). All participant-reported outcomes were similar between groups. Conclusions It was technically feasible to deliver a novel intervention harnessing the online sharing of personal experiences as a tool for smoking cessation, but recruitment was slow and actual use was relatively low, with attrition from the trial. Future work needs to maximize engagement and to understand how best to assess the value of such interventions in everyday use, rather than as an isolated 'dose of information'. Trial registration ISRCTN29549695 DOI10.1186/ISRCTN29549695 . Registered 17/05/2013.